Validation of the educational needs assessment tool as a generic instrument for rheumatic diseases in seven European countries. Issue 12 (6th August 2013) - Ndosi, Mwidimi; Bremander, Ann; Hamnes, Bente; Horton, Mike; Kukkurainen, Marja Leena; Machado, Pedro; Marques, Andrea; Meesters, Jorit; Stamm, Tanja A; Tennant, Alan; de la Torre-Aboki, Jenny; Vliet Vlieland, Theodora P M; et al.
Abstract : Objectives: To validate the educational needs assessment tool (ENAT) as a generic tool for assessing the educational needs of patients with rheumatic diseases in European Countries. Methods: A convenience sample of patients from seven European countries was included comprising the following diagnostic groups: ankylosing spondylitis, psoriatic arthritis, systemic sclerosis, systemic lupus erythematosus, osteoarthritis (OA) and fibromyalgia syndrome. Translated versions of the ENAT were completed through surveys in each country. Rasch analysis was used to assess the construct validity of the adapted ENATs including differential item functioning by culture (cross-cultural DIF). Initially, the data from each country and diagnostic group were fitted to the Rasch model separately, and then the pooled data from each diagnostic group. Results: The sample comprised 3015 patients; the majority, 1996 (66.2%), were women. Patient characteristics (stratified by diagnostic group) were comparable across countries except the educational background, which was variable. In most occasions, the 39-item ENAT deviated significantly from the Rasch model expectations (item–trait interaction χ 2 p<0.05). After correction for local dependency (grouping the items into seven domains and analysing them as 'testlets'), fit to the model was satisfied (item–trait interaction χ 2 p>0.18) in all pooled disease group datasets except OA (χ 2 =99.91; p=0.002). The internal consistency in each group was high (Person Separation Index above 0.90). There was no significant DIF by person characteristics. Cross-cultural DIF was found in some items, which required adjustments. Subsequently, interval-level scales were calibrated to enable transformation of ENAT scores when required. Conclusions: The adapted ENAT is a valid tool with high internal consistency providing accurate estimation of the educational needs of people with rheumatic diseases. Cross-cultural comparison of educational needs is now possible.